(1+cotA)² +(1-cotA)²=2cosec²A
Answers
Answered by
1
Answer:
(1+cotA)^2 + (1-cot)^2
\begin{gathered}\sf \: opening \: the \: brackets \: using \: identity \: \\ \sf {(a + b)}^{2} = {a}^{2} + {b}^{2} + 2ab \: and \\ \sf {(a - b)}^{2} = {a}^{2} + {b}^{2} - 2ab\end{gathered}
openingthebracketsusingidentity
(a+b)
2
=a
2
+b
2
+2aband
(a−b)
2
=a
2
+b
2
−2ab
= 1 + cot^2 A +2cotA + 1 +cot^2 A - 2 cotA
\sf \: 2cot \: a - 2cot \: a = 02cota−2cota=0
So,
= 2 +2cot^2 A
=2(1+cot^2 A)
⏩ Using identity 1+cot^2 A = cosec^2 A
=2 cosec^2 A
= LHS
Hence Proved
\boxed{ \bf{some \: identities}}
someidentities
⏩Sin^2 A + Cos^2A =1
⏩ 1 + Tan^2 A = Sec^2 A
⏩ 1+ Cot^2 A = Cosec^2 A
Similar questions